Fikih Maqasid dalam Fatwa Majelis Ulama Indonesia tentang Penggunaan Vaksin Covid-19 Produk Astrazeneca - Moch. Nurcholis (Tribakti: Jurnal Pemikiran Keislaman, 2021)
The rapid advancement of fiqh discourse has reached a thematic study phase and has shifted to a philosophical style. The philosophical type can be carried out through an integrated combination of fiqh and maqasid al-shari‘ah to produce a fiqh maqasid discourse in the Indonesian Ulama Council’s Fatwa Number 14 of 2021. Fiqh maqasid epistemology also needs to be addressed in this discourse. Efforts to reveal the existence of fiqh maqasid in the MUI fatwa and its epistemological building in this study used content analysis methods and Islamic legal philosophy as the approach. This research concludes that the fiqh maqasid paradigm has been applied in the MUI fatwa by using tarjih based on maqasid al-shari‘ah. In the realm of epistemology, fiqh maqasid originates from transcendental texts supported by ijma‘, and qawa’id al-fiqh. The paradigm in fiqh maqasid involves an integral relationship between ushul al-fiqh, fiqh, reality, maqasid al-shari‘ah, and qawa’id al-fiqh. While the truth in fiqh maqasid is based on the pragmatic theory of truth using instruments of utility, workability, satisfactory consequences.